2021
DOI: 10.3390/insects12070602
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of the Spodoptera litura Chemosensory Protein CSP8

Abstract: Spodoptera litura F. is a generalist herbivore and one of the most important economic pests feeding on about 300 host plants in many Asian countries. Specific insect behaviors can be stimulated after recognizing chemicals in the external environment through conserved chemosensory proteins (CSPs) in chemoreceptive organs, which are critical components of the olfactory systems. To explore its structural basis for ligand-recognizing capability, we solved the 2.3 Å crystal structure of the apoprotein of S. litura … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, the chemical transformation and structure-activity relationship of lauryl alcohol needs further study. The main active constituents of the insecticide obtained from Rhododendron molle is tetracyclic diterpenes with rhodojaponin-III one of the more active components [114,115] . A pot experiment testing the efficacy of rhodojaponin-III against Spodoptera litura larvae showed that after treatment with a concentration of 500 g• mL −1 rhodojaponin-III, the population reduction rate of S. litura was 53.2%, 64.1%, and 79.7% at 1, 3 and 7 days after treatment, respectively.…”
Section: Terpenoidsmentioning
confidence: 99%
“…However, the chemical transformation and structure-activity relationship of lauryl alcohol needs further study. The main active constituents of the insecticide obtained from Rhododendron molle is tetracyclic diterpenes with rhodojaponin-III one of the more active components [114,115] . A pot experiment testing the efficacy of rhodojaponin-III against Spodoptera litura larvae showed that after treatment with a concentration of 500 g• mL −1 rhodojaponin-III, the population reduction rate of S. litura was 53.2%, 64.1%, and 79.7% at 1, 3 and 7 days after treatment, respectively.…”
Section: Terpenoidsmentioning
confidence: 99%
“…According to Lartigue et al [7], CSPs are composed of six -helices with an appropriate molecular weight of 10-12 kDa (or 110-120 amino acid residues), four cysteines that form two tiny loops, two nearby disulfide bridges, and a globular "prism-like" functional structure. Four CSP structures have so far been identified in locusts (Schistocerca gregaria) and moths (Mamestra brassicae, Bombyx mori, and Spodoptera litura) [7][8][9][10][11]. These structures can breathe' or modify their conformation in certain ways in response to ligand binding [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the structures of more than 20 OBPs have been reported in insects [25,26]. By contrast, the structures of very few CSPs are currently available [22][23][24]27]. The three-dimensional structure-based action mechanism of OBPs has been reported in insect species in Lepidoptera, Diptera, and Hemiptera, etc.…”
Section: Introductionmentioning
confidence: 99%